Effect of Educational Intervention on Appropriate Weight Gain in Pregnant Women: A Primary Prevention Approach - E. Abedi Aminloui (Health Education & Health Promotion, 2019)
Aims: A pregnant woman’s nutrition is the main source for fetal development that affects both her and the fetus. The aim of this study was to investigate the effect of educational intervention on appropriate pregnancy weight gain in first-time pregnant women. Materials & Methods: This quasi-experimental study was conducted on 86 first-time pregnant women who attended eight urban health centers in Khorram Darreh, Zanjan, Iran in 2018-2019. The subjects were selected by stratified sampling method and randomly divided into intervention (N=43) and control (N=43) groups. Before intervention, maternal body mass index was measured and the NUTRIKAP questionnaire was used on both groups. The education was provided by a trained nutritionist in three hour-long sessions in the first, second, and third trimesters of pregnancy. The posttest was done immediately after training. At the end of the third trimester, the weight of the pregnant women was measured in both groups. Data were analyzed by SPSS 16 software using independent T, Chi-Square, and Univariate ANCOVA tests. Findings: By controlling the pre-test effect, after the intervention, the mean scores of knowledge (p=0.019) and practice (p<0.001) were significantly different between intervention and control groups, but there was no significant difference between the two groups in terms of attitude variable (p=0.311). The two groups had a statistically significant difference in weight gain during pregnancy (p<0.015). Conclusion: The educational intervention is effective on appropriate pregnancy weight gain in first-time pregnant women.